การกำจัดตะกั่วและแคดเมียมด้วยสารดูดซับจากกระดูกหมู - สุดารัตน์ เลิศวิทยาพนธ์ (จุฬาลงกรณ์มหาวิทยาลัย, 2008)
The research objectives are to study the appropriate preparing conditions of bone adsorbents for the removal of synthetic ion solutions of lead and cadmium(batch and column experiments) and the influential factors to remove them, also study the adsorption isotherm of the two metals and then recovery the spent bone granule with chemical reagents. The physical and chemical characteristics of bone adsorbents were studied and found that the main components are hexagonal structure, calcium hydroxyl-apatite. The results of batch experiment found that the highest percentage and adsorptive capacity of 10 ppm. lead ion by bone char was 1,829 mg. per g. and could remove 99% of lead ion but bone powder was the best adsorbent for cadmium removal, could remove 85% of cadmium ion, the adsorptive capacity was 383 mg. per g. The adsorption isotherms for lead were Freundlich and Langmuir model for bone and bone char respectively and Langmuir model was fitted for cadmium removal by bone adsorbent. The quantities of lead and cadmium removal by bone granule, column test were 4,651 BV. and 4,636 BV. of 30 cm. high of sorbent for 10 ppm. of the metal ion concentration, the flow rate 0.6 lit per hour and the pH solution 4. The best regenerating agent was 5% nitric acid, the regenerating efficiency was 23-25% of original bone granule.